Redescription of Imajimaea draculai—a rare syllid polychaete associated with the sea pen Funiculina quadrangularis - Nygren, A.; Pleijel, F. (Journal of the Marine Biological Association of the United Kingdom, 2010)
We redescribe Imajimaea draculai based on newly collected specimens from the Swedish west coast and describe for the first time its association with the sea pen Funiculina quadrangularis. We assess the phylogenetic position of I. draculai within Autolytinae using nuclear 18SrDNA, together with mitochondrial COI and 16SrDNA, and we estimate its intraspecific variation using nuclear ITS and mitochondrial COI. Our molecular data unequivocally show that I. draculai belongs to the tribe Procerini in a clade consisting of Procerastea, Virchowia and Imajimaea that is separated from all other Procerini taxa for which molecular data are available. No intraspecific variation is found in I. draculai for the sequenced molecular markers.